Determination of antioxidant, anticancer, antidiabetic and antimicrobial activities of Turkish red pine (Pinus brutia Ten.) bark ultrasound-assisted extract as a functional food additive - Erol, Kübra Feyza; Kutlu, Gözde; Tornuk, Fatih; Güzel, Mustafa; Dönmez, İlhami Emrah (Akademiai Kiado Zrt., 2023)
Turkish red pine (Pinus brutia Ten.) is an important tree species that grows widely in Turkiye. In this study, Box-Behnken experimental design was created and optimised for ultrasound assisted extraction of bioactive components of Turkish red pine waste bark. Extraction yield, total phenolic content (TPC), total concentrated tannin (TCT), ferric reducing antioxidant power (FRAP), and 2,2-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) were determined at experimental points. As a result of the optimisation process, optimum parameter values were found at 34.8 8C temperature, 6.5 min time and 116.3 W ultrasonic power. Under optimum conditions, the extraction efficiency was 13.16%, TPC 103.09 mg GAE/g, TCT 13.29 mg CE/g, FRAP 602.14 mg TEAC/g , ABTS 624.51 mg TEAC/g activity results were obtained. The extracts obtained showed low in vitro toxicity against healthy cell lines (HEK-293, human embryonic kidney), proliferation of CaCo-2 (human colorectal adenocarcinoma) , MIA PaCa-2 (human pancreatic adenocarcinoma) cancer cells was significantly reduced. It was also determined that this extract has lower activity against Alzheimer's disease (AD)-associated AChE (acetylcholinesterase)-BChE (butyrylcholinesterase) than diabetes disease associated a-glucosidase and a-amylase. The extracts also showed significant antibacterial activity against Staphylococcus aureus, Bacillus cereus, Listeria mono-cytogenes, Salmonella Typhimurium, and Escherichia coli.
Keywords: Pinus Brutia Ten; Ultrasonication; Antidiabetic; Anticancer Activity; Functional Food Additive